VOx–K2O/γ-Al2O3 catalyst for nonoxidative dehydrogenation of isobutane - Tian, Y.; Bai, P.; Liu, Shaomin; Liu, X.; Yan, Z. (Elsevier, 2016)
V–K/γ-Al2O3 catalysts were prepared using an incipient impregnation method and characterized by N2 adsorption, MAS-NMR, TPR, FT-IR, XPS and Py-FT-IR techniques. The catalytic activity of V–K/γ-Al2O3 in non-oxidative dehydrogenation of isobutane was investigated in a continuous flow packed bed micro reactor. The results indicate that V–K/γ-Al2O3 catalysts display a bifunctional effect. Characterization study suggests that the distribution of various VOx species were influenced by vanadium loadings to a great extent. The catalytic activity of vanadium-based catalysts was consequently promoted to different degrees by diverse VOx species and the highest dehydrogenation activity was obtained for the sample with the highest dispersion of the oligomeric VOx species. The reduced state of vanadium oxide i.e. V3 + and V4 + sites were proved to be the catalytic active sites for dehydrogenation reaction. Moreover, the activity and selectivity of catalysts were strongly related with the acidity of the catalysts. The ratio of Lewis acid sites to Brønsted acid sites (NLS/NBS) was negatively correlated to the isobutene selectivity. Among the tested catalysts, V–K/γ-Al2O3 with an optimum vanadium loading of 10% showed the highest isobutene yield of 42.5%, with ideal stability of presenting yield up to 37.8% after 10 h continuous dehydrogenation reaction.